Peralihan Status Sertifikat Hak Pakai Barang Milik Daerah Menjadi Hak Guna Bangunan : Dalam Kasus Pemanfaatan Aset Mega Mall Kota Bengkulu - Maulana Ramadhan; Suci Wahyuni; Egghy Seliyan Putra; Fadhlur Rizqullah; Muhammad Raziqin Fajri (GLOBAL SCIENTS PUBLISHER, 2026)
Management of regional assets is a crucial aspect of regional governance. Optimizing the utilization of regional assets is expected to increase regional revenues and support local economic development. One form of regional asset utilization is collaboration with the private sector in the development of commercial facilities. However, in practice, the utilization of regional assets often raises legal issues, particularly regarding changes in the status of land rights used in these collaborations. One such polemic case concerns the transfer of the land use rights certificate for land owned by the Bengkulu City Government, used for the construction of the Mega Mall, to a building use rights certificate by the management. This study aims to analyze the legal basis for this change in land rights status, themechanisms that should be followed according to statutory regulations, and the legal implications arising from this change in status for the management of regional assets. The research method used is a normative juridical method with a statutory, conceptual, and case-based approach. The results indicate that the change in the status of use rights to building rights on land owned by the regional government must be carried out through a clear legal mechanism and in accordance with agrarian law and regulations on the management of regional assets. If these changes are not made according to procedure, they could potentially result in losses for the local government and give rise to legal disputes between the local government and the management.